KETERKAITAN ANTARA PENILAIAN KOMPETENSI DENGAN PENILAIAN KINERJA PEGAWAI, SEBUAH STUDI EVALUATIF IMPLEMENTASI MANAJEMEN PEGAWAI NEGERI SIPIL DI BPOM - Meilifa; Wulan Puspita Puri; Perdhana Ari Sudewo; Bintang Aruan (Politeknik STIA LAN Makassar, 2021)
Competence and performance are the main variables in the management of Civil Servants (PNS) in Indonesia, especially in implementing the merit system and talent management. Several researchers have researched the relationship between competence and performance of PNS with mixed results, including a positive and significant correlation, but some studies show no significant correlation between both. Considering that the Government has established policies and regulations related to competency assessment and performance appraisal of PNS, this study aims to conduct an evaluative study of the implementation of policies and regulations through a study of the relationship between competency assessment data and performance assessment data for Pharmacy and Food Supervisory Functional Officials (PFM) at the Indonesian Food and Drug Authority (Indonesian FDA) in 2020. The study population was 1761 PFM functional officials at the Indonesian FDA. The method of determining the sample was carried out using a non-probability sampling technique with a total sample of 177 PFM functional officials. The research was conducted using quantitative research methods through descriptive and correlative statistical analysis. Correlative analysis was carried out with the Pearson Correlation Product Moment statistical test. The research results indicate that the data of assessment of the technical competence of PFM functional positions have a relationship but do not significantly affect the data of the performance assessment of PFM functional officials at the Indonesian FDA in 2020. The results of this study are expected to be used as evaluation resources and input for employees and policymakers in the management of PNS to improve the quality of policies and implement policies of competency assessment and performance appraisals in the management of PNS at BPOM and in Indonesia.